POPULATION’S VULNERABILITY TO NATURAL DISASTERS IN RUNNYMEDE VILLAGE AT TZANEEN LOCAL MUNICIPALITY, SOUTH AFRICA - Matlakala, F.K.; Nyahunda, L.; Makhubele, J.C. (Humanities & Social Sciences Reviews, 2021)
Purpose of the study: This paper was aimed at determining the population’s vulnerability to natural disasters in Runnymede Village at Tzaneen Local Municipality, South Africa. Methodology: The researchers used the qualitative research approach and the exploratory research design. A total number of 16 participants took part in the study. The participants consisted of small-scale farmers, social workers, and disaster management members. Data was collected through individual semi-structured and focus group interviews and was analysed thematically. Main Findings: The study found that impoverished people in the rural areas, people living with disabilities, children, and women are mainly vulnerable to natural disasters. The study thus concludes that people in rural areas are more prone to the impact of natural disasters due to geopolitical, structural, and cultural systems. Applications of this study: People’s relatives, friends, and others close to them can disappear alongside their livelihoods, homes, hospitals, roads, transport, telecommunications networks, and schools. These effects trigger various emotions such as fear, anger, and grief to community members. To this end, community members will receive holistic intervention from relevant social workers, who will be providing psychosocial support. Novelty/Originality of this study: This study contributes positively to the field of social service, and provides guidelines to social workers to address natural disasters. Due to their educational background, social workers should fight the injustices that people in rural areas are predisposed to. They could challenge these injustices (inequalities) as these infringe on individuals’ rights to dignity and other associated rights.